Faktor Penyebab dan Upaya Penanggulangan Tindak Pidana Penganiayaan oleh Anggota TNI yang Mengakibatkan Matinya Warga Sipil di Wilayah Hukum Pengadilan Militer III-15 Kupang - Jundi Nur Wirawan; Rudepel Petrus Leo; Darius Antonius Kian (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
The purpose of this study is to analyze the causal factors and efforts to overcome the criminal act of persecution by members of the TNI which resulted in the death of civilians in the jurisdiction of Military Court III-15 Kupang. Empirical juridical research is legal research on the enactment or implementation of normative legal provisions in every legal event that occurs in society. The results of this study show: (1) there are several factors that cause the persecution committed by members of the TNI which resulted in the death of civilians, namely the motive factor of the perpetrator, economic factors, and law enforcement factors. (2).The countermeasures taken consist of: Preemtiv efforts, Preventive efforts and Repressive Efforts. In accordance with the results of this study, it is hoped that we can appreciate the existence of the existing rule of law so that when an event occurs that relates to the rule of law, then we do not have to take the law into our own hands which will harm ourselves and others.